Epidemiology and adherence to vulvar cancer treatment in western Mexico - Martin-Garibay, Martha (2022)
Objective: To describe the epidemiology, treatment, clinical aspects, and rates of adherence to treat¬ment and follow-up of vulvar cancer in patients treated at the Instituto Jalisciense de Cancerología (IJC) in western Mexico Material y methods: Clinical records of patients with vulvar carcinoma at any clinical stage treated at the IJC during the 2016-2020 period were reviewed. Descriptive statistics were performed with the variables of interest. Results: 53 women with vulvar cancer confirmed by the histopa¬thological study, were studied. At the time of diagnosis, 35.84 % reported a month of evolution; 32.07 %, 6 months; 18.86 %, one year, and 13.2 %, over one year. The tumor size on average was 3,942 cm, and in six patients the size was 1 cm or less. The most frequent initial clinical stage of FIGO was stage III with 37.73 %, followed by stage IB with 28.30 %, and II with 18.86 %. The left labia major is the most commonly affected site, with 22.64 %. 64.15 % of the women abandoned treatment and 83.05 % abandoned follow-up. Conclusions: Squamous cell carcinoma of the vulva is predominant in postmenopausal women with an average age of 66 years. Of 53 cases in 6 years, only 9 continued in follow-up, this implies that most of the patients will have disease progression or even die from it. Most of the patients presented in advanced clinical stages at the time of diagnosis.